2004
DOI: 10.1152/ajpendo.00214.2003
|View full text |Cite
|
Sign up to set email alerts
|

Integration of hormone signaling in the regulation of human 25(OH)D324-hydroxylase transcription

Abstract: . In these cells, cotreatment with the PKC activator TPA and 1,25(OH)2D3 yielded a 27-fold increase in luciferase activity, which was 2-to 3-fold greater than activation obtained with 1,25(OH)2D3 alone (P Ͻ 0.05). Similar results were observed using LLCPK-1 kidney cells, suggesting that the previously observed enhancement of 1,25(OH)2D3-induced renal 24(OH)ase mRNA and activity by PKC activation occurs at the level of transcription. The functional cooperation between PKC activation and VDR was not found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
(83 reference statements)
10
30
0
Order By: Relevance
“…Our findings indicate functional cooperation between C/EBP proteins, CBP (CREB binding protein) and VDR in regulating 24(OH)ase [10]. We also found cooperation between protein kinase C and VDR in the regulation of 24(OH)ase [30]. Our results indicate that the protein kinase C enhancement of 1,25(OH) 2 D 3 stimulated 24(OH)ase transcription may be due, in part, to an increase in VDR concentration and may also be mediated through changes in phosphorylation of VDR coregulators [30].…”
Section: (Oh)d 3 24-hydroxylase (24(oh)ase)supporting
confidence: 64%
See 1 more Smart Citation
“…Our findings indicate functional cooperation between C/EBP proteins, CBP (CREB binding protein) and VDR in regulating 24(OH)ase [10]. We also found cooperation between protein kinase C and VDR in the regulation of 24(OH)ase [30]. Our results indicate that the protein kinase C enhancement of 1,25(OH) 2 D 3 stimulated 24(OH)ase transcription may be due, in part, to an increase in VDR concentration and may also be mediated through changes in phosphorylation of VDR coregulators [30].…”
Section: (Oh)d 3 24-hydroxylase (24(oh)ase)supporting
confidence: 64%
“…We also found cooperation between protein kinase C and VDR in the regulation of 24(OH)ase [30]. Our results indicate that the protein kinase C enhancement of 1,25(OH) 2 D 3 stimulated 24(OH)ase transcription may be due, in part, to an increase in VDR concentration and may also be mediated through changes in phosphorylation of VDR coregulators [30]. In addition, using the human 24(OH)ase promoter, we found that transcriptional activation of VDR from patients with HVDRR (1,25(OH) 2 D 3 resistant rickets; mutant H305Q) can be enhanced by inhibition of phosphatase 1 and 2A ( Fig.…”
Section: (Oh)d 3 24-hydroxylase (24(oh)ase)supporting
confidence: 51%
“…One of the most pronounced effects of vitamin D is to induce the expression of the 25-hydroxy vitamin D3 24-hydroxylase [24(OH)ase] gene, which encodes an enzyme that metabolizes vitamin D. It has been generally believed that vitamin D-mediated transcription of the 24(OH) ase gene is controlled by VDREs located in the proximal promoter region [17,48,49]. However, recent reports indicate that additional upstream VDR binding regions (see Figure 3A) may be also contributing to full vitamin D-responsiveness by the 24(OH)ase gene in osteoblastic cells [50].…”
Section: The 25-hydroxy Vitamin D3 24-hydroxylase Genementioning
confidence: 99%
“…Vitamin D acting through the VDR reacts with the CYP24 promoter region at two positions, -150bp and -250bp. 7 Regulation of CYP24 mRNA depends on the level of circulating 1,25(OH) 2 D 3 . 8 Dwivedi et al reported that ERK1/2 and ERK5 in the MAPK signaling pathway participated in CYP24 promoter induction in monkey kidney fibroblast COS-1 cells.…”
Section: Introductionmentioning
confidence: 99%